Analysis of Influencing Factors Age at First Marriage and Female Fertility in Tembuku District, Bangli District - Kadek Helia Rayani; Ni Nyoman Reni Suasih (International Journal of Economics, Commerce, and Management, 2024)
The population problem faced by almost all developing countries, including Indonesia, is the rate of population growth. A general indicator in population control efforts is the birth rate. Fertility is one of the natural components that determines the rate of population growth, so it is the main indicator in population control efforts. The aim of this research is to determine the effect of education level, employment status, family income, and number of family members, on women's fertility through the age of women's first marriage in Tembuku District, Bangli Regency. This research was conducted in Tembuku District, Bangli Regency. The respondents in this study were 98 female couples of childbearing age using an accidental sampling method . The variables examined in this research are education level, employment status, family income, number of family members, age at first marriage, and female fertility using observation methods, structured interviews and in-depth interviews. The data analysis technique uses path analysis . The results of the research state that 1) Education level, employment status, family income and number of family members have a significant effect on the age at first marriage of women in Tembuku District, Bangli Regency, 2) Education level, employment status, family income and number of family members have a significant effect on women's fertility in Tembuku District, Bangli Regency, 3) Education level, employment status, family income, and number of family members influence women's fertility indirectly through the age of women's first marriage in Tembuku District, Bangli Regency. The level of education, employment status, family income and number of family members will increase the average age at first marriage for women, which will indirectly have an impact on reducing fertility so that it can control the rate of population growth and improve the quality of development economic activities.